2021
DOI: 10.1021/acsnano.1c02709
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Light Emission from Coupled Defect States in DNA-Functionalized Carbon Nanotubes

Abstract: Solid-state single-photon sources are essential building blocks for quantum photonics and quantum information technologies. This study demonstrates promising single-photon emission from quantum defects generated in single-wall carbon nanotubes (SWCNTs) by covalent reaction with guanine nucleotides in their single-stranded DNA coatings. Low-temperature photoluminescence spectroscopy and photon-correlation measurements on individual guanine-functionalized SWCNTs (GF-SWCNTs) indicate that multiple, closely spaced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 40 publications
0
44
0
1
Order By: Relevance
“…Recently, Weisman et al reported a photochemical reaction of DNA-wrapped SWCNTs with singlet oxygen that covalently links guanine (G) to the side wall of SWCNTs (6). Even though the chemical nature of the covalent link was not fully revealed and the structure of the reaction product was rather disordered (9), we are nevertheless motivated to pursue ordered SWCNT lattice modification with the goal of finding more effective ways to explore nanotube chirality and DNA sequence space.…”
mentioning
confidence: 99%
“…Recently, Weisman et al reported a photochemical reaction of DNA-wrapped SWCNTs with singlet oxygen that covalently links guanine (G) to the side wall of SWCNTs (6). Even though the chemical nature of the covalent link was not fully revealed and the structure of the reaction product was rather disordered (9), we are nevertheless motivated to pursue ordered SWCNT lattice modification with the goal of finding more effective ways to explore nanotube chirality and DNA sequence space.…”
mentioning
confidence: 99%
“…[297] Recently, He et al introduced deep-trap states through the reaction of chirality-separated SWCNTs with various aryl functionalization agents, and thus achieved the tunable room-temperature single-photon emission at telecom wavelengths (Figure 17c). [308] These pioneering works have attracted great attentions, and stimulated extensive researches on the mechanisms, property, and applications of covalent functionalization of singlechirality SWCNTs, [275,[296][297][298][299][308][309][310][311][312][313][314][315][316][317][318][319][320][321][322][323][324][325][326] facilitating the development of SWCNT-based single-photon emission.…”
Section: Applications Of Single-chirality Single-wall Carbon Nanotube...mentioning
confidence: 99%
“…[448,454,456,459,460,544] ), carbon nanotubes (black triangles, refs. [476,545,546] ), , III-V epitaxial QDs (red circles, refs. [489,547,548] ), II-VI colloidal QDs (orange circles, refs.…”
Section: Figure 12 Comparison Of Quantum Light Emission Platformsmentioning
confidence: 99%